Croatian Coastal Town Festivals : Production of New Cultural Spaces - Mesarić Žabčić, Rebeka (Array, 2008)
The focus of the proposed article is on festivals on the Croatian coast. They are viewed as practices and cultural spaces that groups recognize as part of their cultural heritage, as defined by the UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage. Festivals are approached as arenas in which cultural identities are built and reasserted, and as a basis for development of cultural tourism. There is a long tradition of the engagement of Croatian researchers in festivals. However, this research was conducted fragmentary, with the emphasis on rural folklore manifestations. Our aim is to address that gap and to study also festivals displaying identities of Croatian coastal towns: Dubrovnik, Split, Omiš, Rab and Motovun. Very different cultural practices will be observed, from displays of traditional forms, over festivities related to patron saints' days, revivals of the medieval heritage, to contemporary performances such as film, street theatre, concerts, modern art exhibitions and so on. The methodology will include the analysis of the published sources, archival research, internet, newspapers and media analysis, opinion polls, but also more qualitative techniques, based mostly upon fieldwork, participant observance and interviews following the oral history approach. The study will address two main issued: analyze festivals as a form of cultural heritage production in Croatia and highlight the attraction basis that Croatian festivals can provide in the development of cultural tourism. The results could be useful to the Croatian, but also other European scientists, since they can provide a basis for comparison of similar phenomena in a wider context. The scientific data can also be built into strategies of making Croatian festival places recognizable at the European tourist market, and, thus, can be communicates to representatives of local communities working on tourism development strategies, but also to consumers of this specific tourism offer.